An Analysis of the 4C Framework (Critical Thinking, Communication, Collaboration, and Creativity) in the Arabic Texts of the Qira’ah ‘Arabiyyah Textbook at Universitas Darussalam Gontor - Mandrasi Amira Sa’idah; Afryandi Pamungkas; Mochammad Fachturrahman Spama Putra (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2025)
In the era of 21st century learning, studying a language is no longer just about mastering grammar and vocabulary. Language education is now expected to foster essential skills such as critical thinking, effective communication, collaboration, and creativity collectively known as the 4C. This study aims to explore how these 4C values are reflected in the Arabic texts found in Qira’ah ‘Arabiyyah, a textbook used in the Arabic Language Education Program at the University of Darussalam Gontor. Using a descriptive qualitative approach and content analysis technique, this research found that all four 21st century skills are indeed present in the analyzed texts. Critical thinking is evident in narratives containing moral dilemmas that encourage readers to draw conclusions; communication appears through the storyline collaboration is reflected in values such as discussion and teamwork and creativity is found in the engaging and varied narrative style. In short, this book is not merely a textbook for learning Arabic, but also a medium that helps students develop essential life skills needed in today’s world